Prevalence of endodontic diseases: an epidemiological evaluation in a Brazilian subpopulation - Bruna Paloma de Oliveira; Andréa Cruz Câmara; Carlos Menezes Aguiar (Universidade Estadual de Campinas, 2017)
Aim: To determine the prevalence of pulp and periradicular diseases in a Brazilian subpopulation, correlating the prevalence with sex, age and most affected teeth. Methods: Data collected from medical records of patients treated at the Clinic of Specialization in Endodontics of the Federal University of Pernambuco between 2003 and 2010. The following variables were recorded for each patient: sex, age, affected teeth and diagnosed endodontic disease. Using Pearson's chi-square and Fisher's exact tests, the collected data analysis was set at a 5% significance level. Results: From all the treated teeth, 57% were diagnosed with pulp diseases, with the symptomatic irreversible pulpitis being the most prevalent (46.3%), while among the diagnosed periradicular diseases (43%), chronic apical periodontitis was the most prevalent (81%). Pulp diseases were detected in men and women in an unequal mode (p=0.008). Subjects under 40 years old had higher prevalence of pulp disease (p=0.286), and patients over 50 years were most affected by periradicular diseases (p=0.439). Maxillary incisors and mandibular first molars were the most affected teeth by endodontic diseases. Conclusions: In the evaluated subpopulation, the endodontic diseases were more prevalente in the maxillary incisive, affected indiscriminately individuals of different age groups and chronic apical periodontitis was the most prevalent diagnosed disease.